The nutritive value and cost of foods consumed by selected individuals over 70 years of age - Combs, May E., author; Dyar, Elizabeth, advisor; Birky, C. W., committee member; Gustafson, Dagmar C., committee member; Guard, Harris T., committee member; Bowman, Ferne, committee member (Colorado State University. Libraries, 1949)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Old age; Diet